Parsing (malicious) pleasures: schadenfreude and gloating at others’ adversity - Leach, Colin Wayne; Spears, Russell; Manstead, Antony S. R. (Frontiers in Psychology, 2015)
We offer the first empirical comparison of the pleasure in seeing (i.e., schadenfreude) and in causing (i.e., gloating) others’ adversity. In Study 1, we asked participants to recall and report on an (individual or group) episode of pleasure that conformed to our formal definition of schadenfreude, gloating, pride, or joy, without reference to an emotion word. Schadenfreude and gloating were distinct in the situational features of the episode, participants’ appraisals of it, and their expressions of pleasure (e.g., smiling, boasting). In Study 2, we had participants imagine being in an (individual or group) emotion episode designed to fit our conceptualization of schadenfreude or gloating. Individual and group versions of the emotions did not differ much in either study. However, the two pleasures differed greatly in their situational features, appraisals, experience, and expression. This parsing of the particular pleasures of schadenfreude and gloating brings nuance to the study of (malicious) pleasure, which tends to be less finely conceptualized and examined than displeasure despite its importance to social relations.